Caso de estudio: IOI's global challenge: moving up the palm oil value chain - Chapoñan Ruiton, Alejandra Lucia (2019)
This research paper presents the business analysis of the company IOI Corporation Berhad (“IOI”), focusing on the financial, logistic and marketing process with the aim of improving the value chain of the company. The business activity of IOI is developed in the plantation and manufacture of oil palm for the export and exploitation of its products. Basically our project contains six chapters to be developed, in the first chapter the objectives are analyzed, through market indicators, to improve the performance of IOI logistics at the international level in the sale of its current and new products to emerging markets. Within the second chapter, reference is made to the research questions which helped determine the company's central path. In chapter three a bibliographical review is made on the theoretical basis of the research since the method used for document collection is very important, it is characterized by the use of available data that have been obtained from secondary sources, with which we work on the project development. Chapter four shows the method used to analyze the information, the qualitative method has been used to understand the current situation of palm oil in the IOI company, understanding the facts of the case and develop criteria that allow determining the validity of the entire information collected. And finally, chapter five provides us with all the information corresponding to the research work on oil palm in the IOI company, based on five important topics: International Market Intelligence, International Marketing, Strategic Global Management, International Trade Logistics and International Financing. Within each theme the theory and practice of the culture and decisions taken by the managers of the company is developed, with the aim of improving the supply chain through innovation.